2020
DOI: 10.1063/1.5140984
|View full text |Cite
|
Sign up to set email alerts
|

The multi-configurational time-dependent Hartree approach in optimized second quantization: Imaginary time propagation and particle number conservation

Abstract: The multi-layer multi-configurational time-dependent Hartree (MCTDH) in optimized second quantization representation (oSQR) approach combines the tensor contraction scheme of the multi-layer MCTDH approach with the use of an optimized time-dependent orbital basis. Extending the original work on the subject [Manthe, Weike, J. Chem. Phys. 146, 064117 (2017)], here MCTDH-oSQR propagation in imaginary time and properties related to particle number conservation are studied. Difference between the orbital equation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 116 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…We note that SQ formulations have previously been introduced in the context of (ML-)MCTDH for systems of indistinguishable particles. 9,27,28,30,31 Our SQ treats distinguishable degrees of freedom (modes) and, thus, differs in the sense that a set of elementary operators is introduced for each mode.…”
Section: Introductionmentioning
confidence: 99%
“…We note that SQ formulations have previously been introduced in the context of (ML-)MCTDH for systems of indistinguishable particles. 9,27,28,30,31 Our SQ treats distinguishable degrees of freedom (modes) and, thus, differs in the sense that a set of elementary operators is introduced for each mode.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems have been treated successfully with different variants of MCTDH [45][46][47][48][49] . As vibrational modes are distinguishable, permutational symmetry is not an issue in quantum molecular dynamics.…”
Section: Mctdh[n] Theory and Extension To Non-adiabatic Dynamics 21 Summary Of Mctdh Theory In Second Quantizationmentioning
confidence: 99%
“…( 2). Recently, Weike and Manthe 48 showed that if the initial SPFs are eigenfunctions of the local particle-number operator of the corresponding k-th sub-Fock space n(k) =…”
Section: Generation Of Initial Spfsmentioning
confidence: 99%
“…Since, as pointed out by Manthe 48 , the SPFs conserve the local particle number, and the propagation of the expansion coefficients of the A-vector conserves the total particle number, MCTDH-SQR calculations based on SPFs with an integer particle number have entries of the A-vector that stay equal to zero at all times. These coefficients refer to configurations of the whole Fock space perpendicular to the initially populated Hilbert space.…”
Section: Generation Of Initial Spfsmentioning
confidence: 99%
See 1 more Smart Citation